Evolution of candidaemia and azole resistance in Italy: A multicentre retrospective study - Anna Prigitano; Anna Grancini; Francesco Barchiesi; Maria Calabrò; Silvia Carletti; Manuela Colosimo; Elena De Carolis; Antonella Lupetti; Gianluca Morroni; Giacomina Pavan; Luisa Romanò; Arianna Tavanti; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Abstract Purpose Candidaemia is the most common healthcare-associated invasive fungal infection. The evolution of the epidemiology of candidaemia in Italy has not been assessed, except at the local level. The primary objective of this study is monitoring changes in the epidemiology of candidaemia and in the susceptibility profiles of Candida isolates between 2015 and 2023. Methods This retrospective multicentre study (2015–2023), involved 11 tertiary-care hospital microbiology laboratories across the Italian country. The confirmed candidaemia episodes were included and demographic data, hospital ward, species identification, and antifungal susceptibility profiles (Sensititre Yeast One) were collected. Results 6,927 candidaemia cases were identified; incidence increased from 1.1/1000 hospitalisations in 2017 to 2.3/1000 in 2020–2021, peaking during the COVID-19 pandemic, and declined in 2023 while remaining above prepandemic levels. Patients older than 65 years accounted for most infections. Medical wards represented the main setting of occurrence, followed by intensive care units, especially during pandemic years. C. albicans remained the most common species (45.4%), followed by C. parapsilosis (24.7%), C. glabrata (11.8%), and C. tropicalis (11.4%). Echinocandin resistance remained low (< 2% for C. albicans and C. glabrata ), whereas azole resistance increased markedly, particularly in C. parapsilosis , reaching fluconazole resistance rates of 25.6% in 2022. Conclusions Candidaemia increased during the 9-year study period in Italy, particularly in the COVID-19 pandemic, in medical wards and ICU. Emerged a growing azole resistance, underscoring the need for enhanced surveillance and informed empirical treatment strategies.